2022
DOI: 10.1155/2022/7813513
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of Neem (Azadirachta indica) Biomass as Bioadsorbent for Removal of Pb2+ Ion from Aqueous Waste Water

Abstract: In this study, neem biomass (a mixture of neem leaf and bark), obtained from the matured neem tree, which is an eco-friendly and low-cost material was selected as a bioadsorbent to remove lead metal ion (Pb2+) from aqueous solutions. Neem biomass-based bioadsorbent having a carboxylic group was prepared by activation using chemical modification by NaOH and citric acid with a very simple method. The optimal activation conditions were determined as 37 min, 120°C, in 0.73 M citric acid, with a sample/acid ratio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Peaks at 1240 cm −1 and 1100 cm −1 may be attributed to stretching vibrations of C-O bonds in the ether and ester groups present in the AI leaves. All these bands indicate the presence of different phytochemicals, such as polyols (phenolic acid and flavonoids), terpenoids and protein compounds in AI leaf extract [37,[39][40][41]. Finally, in the case of ZnO-AI nanocore-shell particles (figure 5(b)), it is observed that all the peaks corresponding to diverse functional groups of phytochemicals (indicated by green colour) coexist alongside the distinctive peaks characterising ZnO NPs (indicated by red colour).…”
Section: Ftir Spectroscopymentioning
confidence: 91%
“…Peaks at 1240 cm −1 and 1100 cm −1 may be attributed to stretching vibrations of C-O bonds in the ether and ester groups present in the AI leaves. All these bands indicate the presence of different phytochemicals, such as polyols (phenolic acid and flavonoids), terpenoids and protein compounds in AI leaf extract [37,[39][40][41]. Finally, in the case of ZnO-AI nanocore-shell particles (figure 5(b)), it is observed that all the peaks corresponding to diverse functional groups of phytochemicals (indicated by green colour) coexist alongside the distinctive peaks characterising ZnO NPs (indicated by red colour).…”
Section: Ftir Spectroscopymentioning
confidence: 91%
“…Zeta potential was measured on Zeta-90Plus particle size analyzer (Brookhaven Instruments Corporation, New York, United States) using a suspension of different samples prepared in water. For the PZC analysis, the salt addition method was used [ 42 ]. The UV–Vis spectroscopy analysis was performed using the PerkinElmer UV/VIS LAMBDA 365+ model (Ahemdabad, Gujarat, India) in wavelength scan and absorbance mode.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, Simić et al [1] achieved a 2.23-times higher capacity of corn silk for Cd(II) ion removal after modification with KOH. Neem biomass chemically pretreated with NaOH and citric acid was confirmed as an efficient biosorbent to remove Pb(II) ions from aqueous solutions [7]. However, recently attention has been devoted to deep eutectic solvents (DES) as innovative green solvents for lignocellulose biomass treatment to procure the desired characteristics for potential further application.…”
Section: Introductionmentioning
confidence: 99%